Assessment of digital competences in Communication students across four Latin American universities - Crawford Visbal, Joseph Livingston (2020)
Professional skills deemed necessary to work in the field of Communication in Latin America have shifted due to the ever more pressing necessities regarding Information and Communication Technologies. This study analyzes the cases of 4 different academic programs in Communications, belonging to 4 universities in the region (Argentina, Colombia, Peru, and Venezuela), comparing their students in 3 phases of their formation (first semester, fourth semester, eight or last semester). We employed questionnaires for new students, focus groups for fourth-semester students, and semi-structured interviews those who were close to graduation. The results reveal that while students do have high levels of internet connectivity, they lack digital competencies such as basic information literacy, which are crucial for their future as professionals.